Limitation of Misconduct of Judges: Increasing The Synergy of Supervision of Judges by The Judicial Commission and The Supreme Court - Fairuz Zahirah Zihni Hamdan; Dwi Rahayu Kristianti; Vincentius Verdian (Yuridika, 2023)
The supervision of judges in judicial power in Indonesia is carried out by two state institutions: the Judicial Commission and the Supreme Court. Internal supervision of judges is carried out by the Supreme Court on the judicial technicalities of judges and externally by the Judicial Commission on the ethical aspects of judge behavior. However, in its implementation, there is still no explicit limit to the scope of judges’supervision between the two institutions. This research aims to provide a different perspective and new breakthrough in judge supervision, namely, setting a boundary between judicial technical violations and ethical violations in examining alleged ethical violations by judges as a form of judicial supervision. The type of research used was reform-oriented research using a statutory and conceptual approach. The results showed that the mechanism for supervising judges was regulated through the Joint Regulations of the Supreme Court and Judicial Commission on the Code of Ethics and Code of Conduct for Judges (KEPPH), KEPPH Enforcement Guidelines, and Joint Examination Procedures. However, in its implementation, there is still a problem of unclear scope and limitations in the supervision of judges. Therefore, there must be improvements in related regulations by limiting technical judicial violations and ethical behavior.